ART IN HONG KONG. (ArtAsiaPacific)
Enid Tsui's book "Art in Hong Kong" provides an insightful analysis of Hong Kong's thriving art scene in the 21st century, emphasizing the city's openness and resilience amidst political challenges. The book explores the growth of the art scene, the impact of the 2019 protests and the Covid-19 pandemic, and the development of cultural institutions like M+. Tsui also delves into the effects of the National Security Law on cultural content in Hong Kong, presenting a nuanced perspective through conversations with key figures in the art community.